"Replaying Life's Tape": Simulations, metaphors, and historicity in Stephen Jay Gould's view of life. (August 2016) - Sepkoski, David
Abstract: In a famous thought experiment, Stephen Jay Gould asked whether, if one could somehow rewind the history of life back to its initial starting point, the same results would obtain when the "tape" was run forward again. This hypothetical experiment is generally understood as a metaphor supporting Gould's philosophy of evolutionary contingency, which he developed and promoted from the late 1980s until his death in 2002. However, there was a very literal, non-metaphorical inspiration for Gould's thought experiment: since the early 1970s, Gould, along with a group of other paleontologists, was actively engaged in attempts to model and reconstruct the history of life using computer simulations and database analysis. These simulation projects not only demonstrate the impact that computers had on data analysis in paleontology, but also shed light on the close relationship between models and empirical data in data-oriented science. In a sense, I will argue, the models developed by paleontologists through simulation and quantitative analysis of the empirical fossil record in the 1970s and beyond were literal attempts to "replay life's tape" by reconstructing the history of life as data. Highlights: The origin of Stephen Jay Gould's metaphor of "Replaying the tape of life" is explained. The history of Gould's participation in evolutionary simulation experiments is discussed. Simulations were an outgrowth of early computing in paleontology. There is a link between simulations and data models in macroevolutionary analysis.